Fabrication of robust protein-based foams with multifunctionality by manipulating intermolecular interactions. Issue 20 (1st October 2021) - Shen, Xingxing; Guo, Qing
Abstract : A useful strategy for the fabrication of mechanically robust protein-based foam with multifunctionality. Abstract : Biopolymer aerogels/foams exhibit wide applications, such as liquid separation and purification, gas separation, catalysis, and thermal insulation. However, their insufficient mechanical stability or complicated fabrication process often limits their practical application. In this work, we describe a facile and sustainable method to prepare robust foams; they are produced from the gelation of whey protein emulsions by manipulating intermolecular interactions. We demonstrate that hydrophobic interactions dominate the sol–gel transition by controlling protein aggregation and determine the linear viscoelasticity of the hydrogel. Blocking the hydrophobic interactions by adding guanidinium hydrochloride (GuHCl) led to a much lower degree of protein aggregation and promoted the formation of intermolecular disulfide bonds, enhancing protein adsorption on to oil droplets and imparting high elasticity to the hydrogel network. When the hydrogel was turned into a foam by freeze drying, the GuHCl foam exhibited outstanding mechanical properties (yield stress: 1.4 MPa; Young's modulus: 16.9 MPa), benefiting from the cellular structure and the synergistic effect of enhanced intermolecular disulfide bonds and oil droplets working as crosslinkers. Also, the foam possessed strong hydrophilicity and underwater oleophobicity (147.8° at pH 10 and 146.7° at pH 0), with resistance to oil fouling, and was successfully used as a filter medium to efficiently separate oil–water mixtures for repeated usage and to rapidly remove cationic dyes from their aqueous solutions. This study provides a universal strategy to design mechanically robust protein-based foams with multifunctionality.